Super Placebos: A Feasibility Study Combining Contextual Factors to Promote Placebo Effects - Olson, Jay A.; Lifshitz, Michael; Raz, Amir; Veissière, Samuel P. L. (Frontiers in Psychiatry, 2021)
Ample evidence demonstrates that placebo effects are modulated by contextual factors. Few interventions, however, attempt to combine a broad range of these factors. Here, we explore the therapeutic power of placebos by leveraging factors including social proof, positive suggestion, and social learning. This study aimed to test the feasibility of an elaborate "super placebo" intervention to reduce symptoms of various disorders in a pediatric population. In a single-arm qualitative study, participants entered an inactive MRI scanner which they were told could help their brain heal itself through the power of suggestion. The sample included 11 children (6-13 years old) diagnosed with disorders known to be receptive to placebos and suggestion (Attention Deficit Hyperactivity Disorder, Tourette Syndrome, chronic skin picking, and migraines). The children were given positive suggestions during 2 to 4 "placebo machine" sessions over the span of approximately one month. We assessed open-ended treatment outcomes via recorded interviews and home visits. The procedure was feasible and no adverse events occurred. Ten of the eleven parents reported improvements in their children after the intervention, ranging from minor transient changes to long-term reductions in subjective and objective symptoms (e.g., migraines and skin lesions). These preliminary findings demonstrate the feasibility and promise of combining a broad range of contextual factors in placebo studies. Future research is needed to assess the causal effects of such interventions.